(3fLGI GdYGedjfs - (3GdNGbGfj, MSf Hf Ydj, b (B14s
(3ChdgG (B:s
(3GdMeO ddg (B... (3eSFdI jdRe cd ecda Cf jchf Yedg ef YHGOGJ heYGedI JQaj aj ZjQ GdVQQ (B.. (3EeG HGLJgGO Ch JbdjO dG KGdK aj GdHjf Ydi GdCbhi ceG gh (B.. (3EP LhGR GdGMJjGW jdRe ajg Cf jchf YGQaG HcjajJg EeG HGLJgGO Ch JbdjO (B....s
(3BNQgG (B:s
... (3ef GdfU GdOGd Ydi GdJMed YfgG aj Uhe QeVGf hEf cGfJ YjQ ecQgI Hd eWGhYI aYd cd efgeG cqaGQJGf Ef cGf aj GdfgGQ hcaGQI hGMOI Ef cGf aj Gddjd Je cJGa GdGYJcGa hdg GdMeO(B.s
(3GdJhKjbGJ GdeQLYjI (B:s
(3QLGd GdNGbGfj (B30s
(3QLGd GdNGbGfj (B31s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis